2018
DOI: 10.3892/mco.2018.1583
|View full text |Cite
|
Sign up to set email alerts
|

Large-cell neuroendocrine carcinoma arising in the endometrium: A case report

Abstract: Large-cell neuroendocrine carcinoma (LCNEC) of the endometrium is an extremely rare, high-grade malignant tumor. We herein report a case of a rapidly growing LCNEC arising in the endometrium. A 52-year-old woman was referred to Toyooka Hospital (Tooyoka, Japan) due to genital bleeding in February 2016. There had been no abnormalities on a regular gynecological and physical examination 3 months prior to the consultation. Imaging (computed tomography and magnetic resonance imaging) and a pelvic examination revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The average age of 42 patients with endometrial SCNEC at the time of diagnosis was reported to be 60 years old, 3 while Ogura et al 11 noted ages ranging from 40 to 88 years (mean 62 years) for 19 cases of endometrial LCNEC. In a series of 25 patients with endometrial NEC (LCNEC 15, SCNEC 4, mixture of both 6), patient age ranged from 37 to 87 years (median 57 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average age of 42 patients with endometrial SCNEC at the time of diagnosis was reported to be 60 years old, 3 while Ogura et al 11 noted ages ranging from 40 to 88 years (mean 62 years) for 19 cases of endometrial LCNEC. In a series of 25 patients with endometrial NEC (LCNEC 15, SCNEC 4, mixture of both 6), patient age ranged from 37 to 87 years (median 57 years).…”
Section: Discussionmentioning
confidence: 99%
“…If MRI can be shown to correctly diagnose endometrial NEC and provide accurate staging prior to treatment, it would be utilized as a helpful clinical tool. To the best of our knowledge, only four case reports discussing the MRI characteristics of endometrial LCNEC have been presented, [8][9][10][11] while none are known to include discussion of MRI findings of endometrial SCNEC, thus the MRI features of endometrial NEC are not well understood. The aim of this study was to identify distinct features as well as staging accuracy of endometrial NEC shown by MRI, including SCNEC and LCNEC.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of neuroendocrine tumors of the endometrium are SCNEC; they account for approximately <1% of all endometrial carcinomas. LCNEC of the endometrium is considered rarer than SCNEC [4567]. To date, there have only been 2 reports of carcinoid tumors of the uterine corpus [89].…”
Section: Introductionmentioning
confidence: 99%
“…Large cell neuroendocrine carcinoma (LCNEC) is a high-grade neoplasm most commonly presenting in the lung, although it has been noted in the literature to occasionally arise in other locations including the gastrointestinal tract, bladder, prostate, gallbladder, ovary, uterus and submandibular gland (1)(2)(3)(4)(5)(6)(7). LCNEC is a rare cancer, estimated to comprise between 2.1 and 3.5% of surgically resected lung tumors (8,9).…”
Section: Introductionmentioning
confidence: 99%